2020
DOI: 10.3892/mco.2020.2170
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic relevance of high pretreatment CA125 levels in primary serous ovarian cancer

Abstract: The objective of the present study was to analyze the prognostic relevance of pretreatment serum CA125 ≥500 U/ml and its role as a non-invasive factor for estimating optimal cytoreduction (≤1 cm) in primary serous ovarian cancer. Clinicopathological parameters and CA125 levels prior to primary cytoreductive surgery were retrospectively evaluated in all 261 consecutive patients with primary epithelial ovarian cancer from a single centre. Inclusion criteria were existing preoperative CA125 level, serous ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, the effect of CA125 on the prognosis of advanced EOC remains controversial. Studies have shown that PFS and OS are significantly better in advanced FIGO stage EOC when CA125 is <500 U/mL than when CA125 is >500 U/mL ( 28 ). However, there are studies that argue against it.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of CA125 on the prognosis of advanced EOC remains controversial. Studies have shown that PFS and OS are significantly better in advanced FIGO stage EOC when CA125 is <500 U/mL than when CA125 is >500 U/mL ( 28 ). However, there are studies that argue against it.…”
Section: Discussionmentioning
confidence: 99%
“…Blood biomarkers such as preoperative Hb and Ca125 were not included as they appear more reliable to predict surgical outcomes or simply predict malignancy in women with adnexal masses. 16 , 17 Equally, surveillance modalities are not used to comprehensively evaluate the prognosis of the HGSOC patients provided that the primary objective of follow-up is to detect disease that if treated early can extend survival. It is not to prolong time living with the knowledge that cancer has relapsed without extending survival.…”
Section: Methodsmentioning
confidence: 99%
“…In clinical practice, measuring the serum level of CA-125 was found to be useful at different points of OC management. Increased pretreatment CA-125 levels are an independent predictor of PFS and OS 5 , 6 . A postoperative decline in serum CA125 levels (> 75% or ≥ 80%) was found to be an independent prognostic factor for progression-free survival 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%